Characteristics of neonicotinoid imidacloprid in urine following exposure of humans to orchards in China. (November 2019) - Tao, Yan; Dong, Fengshou; Xu, Jun; Phung, Dung; Liu, Qianyu; Li, Runan; Liu, Xingang; Wu, Xiaohu; He, Min; Zheng, Yongquan
Abstract: Imidacloprid (IMI) is a typical neonicotinoid with the largest usage in agricultural orchards in China. The long-term repeated use and the lack of proper protective measures may result in rural farmers and people living near orchards to be inevitably exposed to IMI. Excessive exposure may cause potential adverse effects on human health. To explore the characteristics of human exposure to IMI in urine, different groups of people, including pesticide applicators and their family members, and kindergarten children near IMI-applied orchards were investigated. The IMI and metabolite, 6-chloronicotinic acid (6-CNA), concentrations in urine were creatinine-adjusted to compensate for a possible dilution effect. Target analytes were detected in 100% of 1926 urine samples. The results showed that the IMI concentration in the 1-d urine from the rural residents significantly increased after a spraying event ( p < 0.05) and reached the highest concentration (Geomean: 16.42 μg/g creatinine for IMI; 7.33 μg/g creatinine for 6-CNA) in the 2-d urine samples. The pesticide applicators of different genders had almost the same exposure environment (IMI Geomean of 13.25 μg/g creatinine for males and 14.71 μg/g creatinine for females) ( p > 0.05). Females had higher exposure concentrations than that of males. People from different villages demonstrated diverse exposure levels with Geomean differences of 1.13–3.28 fold. For 3–6 years-old children, urinary concentrations from the rural group (Geomean: 3.73 μg/g creatinine for IMI; 3.95 μg/g creatinine for 6-CNA) were significantly higher than that of the urban group (Geomean: 1.13 μg/g creatinine for IMI; 0.88 μg/g creatinine for 6-CNA) ( p = 0.00001), and the younger children tended to have higher exposure risk. Our findings showed that people in the Henan orchard areas were likely exposed to IMI to varying degrees. Further research on the health risk evaluation of IMI and controlling the exposure risks is needed. Highlights: Imidacloprid and major metabolite 6-CNA was detected in 100% of urine samples. Urinary levels of imidacloprid and 6-CNA increased markedly after spraying event. Rural children have 3.30–4.49 folds higher imidacloprid exposure than urban ones. The adolescent and elder have higher imidacloprid exposure. People from 9 villages showed 1.13–3.28 folds of imidacloprid exposure difference.